TRANSFORMATION PROCESSES IMPLEMENTED IN THE BANKING SYSTEM AND POSSIBILITIES OF IMPLEMENTING IT IN OUR COUNTRY (International journal of artificial intelligence, 2025)
The article discusses the goal of the New Uzbekistan Development Strategy for 2022-2026, which sets the goal of "making the digital economy the main "driver" sector and increasing its volume by at least 2.5 times", and the task of completing the transformation processes in state-owned commercial banks and bringing the share of private banks in bank assets to 60 percent by the end of 2026. The main driver of the development of the banking system, increasing mutual trust and transparency between the bank and the client, and the consequences of modernization without the rapid implementation of the latest achievements of scientific and technological progress in banking activities, as well as in-depth studies of world practice and influencing factors are analyzed.